The Effect of Parent's Interaction on Early Childhood’s Emotional Intelligence - Ari Sofia; Vivi Irzalinda (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
AbstractThis study aimed to analyze the influence of parents' interactions on emotional intelligence in early childhood. The subjects of this study amounted to 55 people who were selected by purposive sampling technique, with the characteristics of having early childhood aged 4-5 years. Subjects are parents who live on Pasaran Island, Bandar Lampung. The data collection technique used a questionnaire, consisting of a parent interaction questionnaire and an emotional intelligence questionnaire for early childhood. The data analysis technique used regression analysis. The results showed that there was a effect of parental interaction on early childhood emotional intelligence (β= 0.432, p= 0.00 (p<0.01), and effective contribution = 36.6%). Keywords: early childhood, emotional intelligence, parental interaction. AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh interaksi orang tua terhadap kecerdasan emosi anak usia dini. Subjek penelitian ini berjumlah 55 orang yang dipilih dengan teknik purposive sampling, dengan karakteristik memiliki anak usia dini berusia 4-5 tahun. Subjek adalah orang tua yang tinggal di Pulau Pasaran Bandar Lampung. Teknik pengambilan data menggunakan kuesioner, terdiri dari kuesioner interaksi orang tua dan kuesioner kecerdasan emosi anak usia dini. Teknik analisis data menggunakan analisis regresi. Hasil penelitian menunjukkan ada pengaruh interaksi orang tua terhadap kecerdasan emosi anak usia dini (β= 0.432, p= 0,00 (p<0,01), dan sumbangan efektif = 36,6%). Kata Kunci: anak usia dini, kecerdasan emosi, interaksi orang tua.